Electrochemistry for bioanalysis - Patel, Bhavik A. (Elsevier, 2021)
"Electrochemistry for Bioanalysis provides a comprehensive understanding of the benefits and challenges of the application of electrochemical and electroanalytical techniques for measurement in biological samples. The book presents detailed information on measurement in a host of various biological samples from single cells, tissues and in vivo. Sections cover real insights surrounding key experimental design and measurement within multiple complex biological environments. Finally, users will find discussions on emerging topics such as electrogenerated chemiluminescence and the use of additive manufacturing for biosensor fabrication. Continuous learning reinforcement throughout the book, including problems for self-assessment, make this an ideal resource" -- $$c Provided by publisher.